Volume 2: 28th Biennial Mechanisms and Robotics Conference, Parts a and B 2004
DOI: 10.1115/detc2004-57064
|View full text |Cite
|
Sign up to set email alerts
|

A More General Mobility Criterion for Parallel Platforms

Abstract: This contribution presents a more general mobility criterion applicable to parallel platforms, unlike previously employed mobility criteria based on the well-known Kutzbach-Gru¨bler criterion that often fails to provide the correct number of degrees of freedom of parallel manipulators, the mobility criterion introduced in this contribution provides the correct number of degrees of freedom for a wider class of parallel manipulators. Furthermore, the analysis provides insight into why the criteria based on the K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 0 publications
0
14
0
2
Order By: Relevance
“…The approach in Dai et al [2006] is based on the constraint space formulation. It is also shown that the mobility can be found by the motion space as in Rico et al [2003] and Rico et al [2006]. By this approach the chains are also classified and it is straight forward to determine the effect a passive joint has on the mechanism.…”
Section: Overconstrained Mechanismsmentioning
confidence: 99%
See 4 more Smart Citations
“…The approach in Dai et al [2006] is based on the constraint space formulation. It is also shown that the mobility can be found by the motion space as in Rico et al [2003] and Rico et al [2006]. By this approach the chains are also classified and it is straight forward to determine the effect a passive joint has on the mechanism.…”
Section: Overconstrained Mechanismsmentioning
confidence: 99%
“…In the following, we will show that an alternative to the Modified Grübler formula given in (30) can be found from the motion space and we will show how this approach naturally leads to the classification of different types of overconstrained joints. This is the same classification of overconstrained chains as in Rico et al [2003] and Rico et al [2006]. Further, in the next section, we will use this to set up a set of simple rules on where the active joints need to be placed, i.e.…”
Section: The Motion Spacementioning
confidence: 99%
See 3 more Smart Citations